“É diferente? Isola”: jovens LGBTQIA+ no Sistema Socioeducativo - Sousa, Bruno Alves de (2021)
The research context is the Juvenile Justice System in Ceará. The main subject is understanding how sexual and gender experiences of adolescents and young people identified as LGBTQIA+ are crossed by the experience of arrest. The methodology is eminently qualitative. For this, I researched on internet news and public documents. The bibliographic survey included imprisonment of LGBT adults and educational measures. In the fieldwork, I followed events with subjects of public policies for childhood and adolescence and sexual diversity, in addition to informal conversations with interlocutors. During this time, the Covid-19 pandemic spread and methodological adaptations were necessary. Therefore, I conducted interviews through virtual platforms with three young people from male and female centers, supported by the Public Prosecutor’s Office in Ceará, and with professionals in these government areas. I noticed the little visibility of these subjects, caused by absence of specific regulations. Concern about violence in these centers and attacks on civil rights in the public arena have left such people in the margins of these policies.